Model Komunikasi Kepala Kantor Urusan Agama (KUA) dalam Meminimalisir Angka Perceraian - Yuyun Putri; Erman Anom (IPM2KPE, 2023)
This study aims to determine the communication model used by the Balaraja District Office of Religious Affairs (KUA) in minimizing the divorce rate in Balaraja District, Tangerang Regency, Banten Province. The research method used is qualitative, with a case study type of research. The results showed that the communication model used by the Office of Religious Affairs (KUA) in Balajara District in minimizing the divorce rate in Balaraja District used the Lasweell model of communication and the Stimulus-Response (S-R) communication model. Where the Office of Religious Affairs (KUA) of Balaraja District, in carrying out its activities, always conducts a communication analysis that includes elements of effective communication which in the end sees how the response obtained from the stimulus results goes according to purpose or not. In conclusion, the communication model used has not had a significant impact, meaning that it still increases the divorce rate in Balaraja District. However, the communication model that is carried out makes a good contribution to married couples who are going to divorce in the form of consideration in making a decision to divorce. Keywords: Divorce Rate, Communication Model